2018
DOI: 10.1111/apa.14610
|View full text |Cite
|
Sign up to set email alerts
|

Higher parental education was associated with better asthma control

Abstract: Aim Inhaled corticosteroids have resulted in the improved control of asthma and a reduced need for hospitalisation. This study aimed to examine the prevalence of uncontrolled asthma and factors that affect asthma control. Methods The data came from a longitudinal cohort study of children. The parents answered questionnaires from age 6 months to 12 years. The response rate at age 12 years was 76% (3637/4777) and doctor‐diagnosed asthma was reported in 6.4% (n = 233). Asthma control was examined with the Asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(45 reference statements)
3
10
0
Order By: Relevance
“…Approximately, a third of our study participants indicated controlled asthma. The higher level of parental education was significantly associated with better asthma control, which is consistent with a recent study in Sweden among pediatric asthma patients 33 . Asthma control for children mainly relies on parental ability to monitor symptoms, use medication, and follow an asthma action plan at home 32 .…”
Section: Discussionsupporting
confidence: 88%
“…Approximately, a third of our study participants indicated controlled asthma. The higher level of parental education was significantly associated with better asthma control, which is consistent with a recent study in Sweden among pediatric asthma patients 33 . Asthma control for children mainly relies on parental ability to monitor symptoms, use medication, and follow an asthma action plan at home 32 .…”
Section: Discussionsupporting
confidence: 88%
“… 33 Conversely, a higher education in parents has been found to be associated with better asthma control in children. 48 Several comorbidities and conditions, such as allergic rhinitis, obesity, gastroesophageal reflux disease, psychological disturbances, and obstructive sleep apnea, are frequently observed in patients with asthma and may impact the clinical manifestation and severity of asthma. 49 , 50 Of note, the prevalence of psychiatric comorbidities, such as anxiety and depression, is high in patients with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…19,36,37 Maternal education of more than 12 years was protective against admissions in infants with recurrent asthma-like symptoms, which agrees with other studies in older children, showing that higher parental education is related to better asthma control. 38 It is worth mentioning that although we found the highest income (household income of ≥US$ 3,000 per month) was a significant protective factor for admissions, it would be misleading because it represented just the 4.5% of infants with asthma-like symptoms studied.…”
Section: Discussionmentioning
confidence: 64%